The Political Economy of Privatization - Bernardo Bortolotti; Paolo Pinotti (Fondazione Eni Enrico Mattei (FEEM), 2003)
This paper provides an empirical analysis of the role of political institutions in privatization. The empirical testing relies on a new political database with continuous and time-varying measures of the political-institutional setting, and of the partisan orientation of the executive. Using panel data for 21 industrialized countries in the 1977-1999 period, first we show the likelihood and the extent of privatization to be strongly and positively associated with majoritarian political systems. On the contrary, in consensual democracies privatization seems delayed by a war of attrition among different political actors. Second, we identify a partisan determinant of the choice of the privatization method. As theory predicts, right wing executives with re-election concerns design privatization to spread share ownership among domestic voters.
Keywords: D72; D78; L33; 330; Political institutions; Partisan politics; Privatization; Privatisierung; Ökonomische Theorie der Demokratie; Industrieländer